RANCANG BANGUN SISTEM APLIKASI PENGAJUAN EVENT DAN NOTIFIKASI REAL TIME MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS BERBASIS WEBSITE PADA BUILDING MANAGEMENT BINUS - Anggelia Wijayanti; Aa Kurniawan (Informatika: Jurnal Teknik Informatika dan Multimedia, 2026)
This study designs a web-based application that manages event submissions integrated with material requests and real-time notifications to streamline the operational workflow of BINUS Building Management. Material requests can only be created once the corresponding event has been approved, ensuring a more controlled and traceable process. The Analytical Hierarchy Process (AHP) is applied to objectively determine event submission priorities based on predefined criteria. The development process involves identifying user needs, designing the system architecture, implementing the required features, and evaluating their functionality. The system improves the sequence and organization of material requests after event approval and accelerates communication through instant notifications delivered to relevant parties, including the ISS team. The findings indicate enhanced efficiency in handling submissions and approvals, reduced communication errors, and more accurate data processing, ultimately supporting better overall operational performance for BINUS Building Management.